FitBack – evropska mreža za podporo spremljanja telesne zmogljivosti otrok in mladostnikov - Jurak, Gregor (Šport (Ljubljana), 2023)
The FitBack project has developed a specific, custom-made, multi-lingual web platform to analyse data from the most used physical fitness tests for children and adolescents adopted in Europe. The platform can provide individual feedback with reference values regarding the European population and potential health risk of the individual. This educational and health diagnostic tool is available to all users free-of-charge, in the hopes that the interactive tool and materials can improve the fitness of its target groups, including: teachers, parents, adolescents, physicians, coaches and anyone interested in evaluating, analysing and monitoring physical fitness data. The FitBack platform facilitates increasing physical literacy, motivates stakeholders to participate in physical activity interventions, including establishing their own fitness monitoring system, an essential first step to better understand the current local, regional, or national fitness of children and adolescent populations. This paper presents background information on how to use the web platform, how to create individual and group reports, and how the information can be used to assist physical education teachers to construct more efficient pedagogical processes aimed to the specific needs of their students.
Keywords: gibalna pismenost; javno zdravje; mladostniki; otroci; pedagogika; šport; športna vzgoja; telesna aktivnost; zdravstveno tveganje